Dynamical cluster disruption and its implications for multiple population models in the E-MOSAICS simulations - Reina-Campos, Marta; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Several models have been advanced to explain the multiple stellar populations observed in globular clusters (GCs). Most models necessitate a large in